Hierarchical TiO2 nanoflakes and nanoparticles hybrid structure for improved photocatalytic activity - Tang, Yuxin (2013)
Three-dimensional TiO2 microspheres with different hierarchical nanostructures were synthesized by the synergistic strategies of ultrafast electrochemical spark discharge spallation process followed by thermal treatment. The morphology, crystal structure, surface area, and photocatalytic activity of the hierarchical nanostructures were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, surface area analysis, and UV–vis spectroscopy respectively. The nanostructure of hierarchical microspheres undergoes three evolution steps, which includes the change from nanosheets into hybrid nanoflakes/nanoparticles and finally to nanoparticles as calcination temperature increases, in line with the predicable trend of increase in crystallinity and decrease in specific surface area. Compared to other forms of calcined TiO2 samples (nanosheets and nanoparticles), the hybrid TiO2 nanoflake/nanoparticle hierarchical porous structure exhibits a higher photocatalytic activity for the degradation of organic compounds (methyl orange and bisphenol A). This is attributed to their larger specific surface area (116 m2/g), more abundant porosity, and good crystallinity. On the basis of this hybrid structure, a visible light sensitive Ag/TiO2 microsphere photocatalyst is designed which shows faster degradation rate under the visible light illumination (>420 nm). The porous microspheric photocatalyst does not lose its activities after recycled use, showing great potential for practical application in environmental cleanup.